OPERATOR BATAS PADA HOMOLOGI KUBIK - Sulastri . (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
Algebra topology is a concept that classifies topological spaces particularlycubical sets based on the context of the algebraic objects namely homology groups. Atopological problem can also be viewed from the point of view of combinatorics whichcan be simplified to be graphs. In this paper it is discussed about the classification ofthe cubical sets based on its homology groups using the concept of boundary operatorsas homomorphisms of free Abelian groups.